2020
DOI: 10.21203/rs.3.rs-120581/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High incidence of stroke and mortality in pediatric critical care patients with COVID-19 in Peru

Abstract: Introduction: Pediatric critical care patients with COVID-19 treated in Peru have higher mortality than those previously reported from other countries. Pediatric providers have reported a high number of patients without comorbidities presenting with hemorrhagic strokes associated with COVID-19. We present a study analyzing the factors associated with mortality in this setting.Methods: Prospective case-control study that included patients < 17 years old admitted to a pediatric critical care unit with a posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…37 Also, there are reports regarding differences in mortality between high and lowmiddle-income countries. 39,40 It is very interesting that in the current study, previous known variables associated with mortality in PARDS and in pediatric critical COVID-19, like organ failures and hypoxemia severity, were not different between survivors and non-survivors. 37,38,[41][42][43][44][45] A surprising result was the difference in the respiratory mechanics between the clinical phenotypes.…”
Section: Discussionmentioning
confidence: 53%
“…37 Also, there are reports regarding differences in mortality between high and lowmiddle-income countries. 39,40 It is very interesting that in the current study, previous known variables associated with mortality in PARDS and in pediatric critical COVID-19, like organ failures and hypoxemia severity, were not different between survivors and non-survivors. 37,38,[41][42][43][44][45] A surprising result was the difference in the respiratory mechanics between the clinical phenotypes.…”
Section: Discussionmentioning
confidence: 53%
“…3 A smaller series of 47 patients with SARS-CoV-2 admitted to the intensive care unit at two sites in Peru demonstrated stroke in 12.8% of patients (6 of 47 patients). 57 Notably, hemorrhagic stroke was more common than ischemic stroke in this cohort. Overall, at least 26 studies have been reported of pediatric patients with stroke related to COVID-19 infection (►Table 2).…”
Section: Arterial Ischemic and Hemorrhagic Strokementioning
confidence: 75%
“…[15][16][17][18]53 Studies demonstrate that many affected patients have at least one preexisting risk factor for stroke. 3,8,57 Mechanical thrombectomy can be successfully used to treat large-vessel occlusion in the setting of SARS-CoV-2. 59 Despite treatment, studies suggest that SARS-CoV-2-related stroke in children results in greater mortality than infection or MIS-C alone.…”
Section: Arterial Ischemic and Hemorrhagic Strokementioning
confidence: 99%
See 2 more Smart Citations